2017
DOI: 10.1634/theoncologist.2017-0335
|View full text |Cite
|
Sign up to set email alerts
|

Management of Adverse Events Associated with Cabozantinib Therapy in Renal Cell Carcinoma

Abstract: Cabozantinib leads to improved survival outcomes in renal cell carcinoma patients compared with everolimus. However, management of the adverse event profile is crucial to achieve optimum adherence and outcomes with the use of cabozantinib. This review aims to provide appropriate guidance that will minimize the impact of adverse events and help to maximize the utility of this agent in patients with advanced renal cell carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 108 publications
(191 reference statements)
1
42
0
3
Order By: Relevance
“…Consequently, it has been suggested that VEGFR and c-Kit inhibition may cause diarrhoea [28]. Management of HFSR, diarrhoea and hypertension is especially important; although they are associated with positive treatment outcomes, they are among the most frequently experienced AEs [2][3][4][5].…”
Section: Association Of Tki Aes With Positive Treatment Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, it has been suggested that VEGFR and c-Kit inhibition may cause diarrhoea [28]. Management of HFSR, diarrhoea and hypertension is especially important; although they are associated with positive treatment outcomes, they are among the most frequently experienced AEs [2][3][4][5].…”
Section: Association Of Tki Aes With Positive Treatment Outcomesmentioning
confidence: 99%
“…Use of a food diary may be helpful for identifying particular items that exacerbate diarrhoea [51]. Additionally, consumption of bananas, rice, potatoes, apple sauce, toast and probiotics may help to alleviate symptoms [28,53]. It is important to ensure that patients with diarrhoea do not become dehydrated; fluid intake should be increased, and electrolytes monitored and replaced when necessary [36,40,43,45,47].…”
Section: Diarrhoeamentioning
confidence: 99%
See 1 more Smart Citation
“…If patients do not have cardiovascular comorbidity, angiotensin receptor blockers may be the agent of choice as they have been shown to inhibit angiotensin II-mediated growth and migration of cancer cells and angiogenesis. β-Blockers may also have some role in reducing hypertension induced by VEGF pathway inhibitors as they have shown to induce apoptosis in endothelial cells [19]. Our patient was started on amlodipine and metoprolol, which controlled her blood pressure well; ACE inhibitors were not used due to her underlying kidney disease.…”
Section: Discussionmentioning
confidence: 92%
“…The widespread diffusion of cabozantinib in the treatment algorithm of mRCC raised the question about the clinical effects of its exposure on cardiac function. Of note, the development of hypertension as a result of cabozantinib therapy represents 1 of the most frequently reported side effects, with an incidence of 37% in the METEOR trial (15% of grade 3–4) and of 81% in the CABOSUN study (28% of grade 3–4) . A meta‐analysis of randomized trials of cabozantinib (in different indications) confirmed the increased risk of developing all‐ and high‐grade hypertension, the latter of which had a substantially higher frequency compared to other approved VEGFRs‐TKIs (sorafenib, sunitinib, and pazopanib) .…”
Section: Discussionmentioning
confidence: 95%